PENGARUH KOMITMEN PIMPINAN, PENGENDALIAN INTERNAL DAN KOMPETENSI TERHADAP KINERJA PENGELOLA KEUANGAN PEMERINTAH KOTA PALU - Siswoyo, Rudi (Katalogis, 2018)
The study aimsto determine and analyze simultaneous and partial influence of leader’s commitment, internal monitoring, and competency on the performance of financial administrator of Palu City Government. Sample of study selected through purposive sampling, consists of 90 financial administrators in 30 governmental working units in Palu City. Method of analysis is multiple linear regressions. The result underlines that leader’s commitment, internal monitoring and competency simultaneously have significant influence on the performance of financial administrators. Partial test shows that each variables of leader’s commitment, internal monitoring, and competency have significant influence on the performance of financial administrators.